A broadly tunable synthesis of linear α-olefins. Issue 1 (December 2017) - Gollwitzer, Andreas; Dietel, Thomas; Kretschmer, Winfried; Kempe, Rhett
Abstract The catalytic synthesis of linear α-olefins from ethylene is a technologically highly important reaction. A synthesis concept allowing the formation of selective products and various linear α-olefin product distributions with one catalyst system is highly desirable. Here, we describe a trimetallic catalyst system (Y–Al–Ni) consisting of a rare earth metal polymerization catalyst which can mediate coordinative chain transfer to triethylaluminum combined with a simultaneously operating nickel β-hydride elimination/transfer catalyst. This nickel catalyst displaces the grown alkyl chains forming linear α-olefins and recycles the aluminum-based chain transfer agent. With one catalyst system, we can synthesize product spectra ranging from selective 1-butene formation to α-olefin distributions centered at 850 gmol−1 with a low polydispersity. The key to this highly flexible linear α-olefin synthesis is the easy tuning of the rates of the Y and Ni catalysis independently of each other. The reaction is substoichiometric or formally catalytic regarding the chain transfer agent. Linear α-olefins are important bulk chemicals annually produced in megaton scale. Here, the authors report a trimetallic catalyst system for the synthesis of 1-butene and a broad range of α-olefins and achieve control over chain length by tuning the reaction rates of the nickel and yttrium catalysts.